(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article analyzes the history and stages of development of oratory as a significant cultural, social and educational phenomenon. Oratory is not merely the ability to speak beautifully in front of an audience; it is a complex communicative skill that includes logical thinking, linguistic accuracy, emotional influence, ethical responsibility and audience awareness. The article examines the formation of oratory from ancient oral traditions to classical Greek and Roman rhetoric, medieval religious eloquence, Renaissance humanistic speech, Enlightenment public debate and modern digital communication. The research is based on historical-comparative and theoretical-analytical methods. Special attention is paid to the concept, content, structural elements, formation factors, practical application, current problems and development perspectives of oratory. The findings show that oratory developed in close connection with social needs, political systems, educational traditions, religious institutions and technological changes. In modern education, oratory plays an important role in developing students’ communicative competence, critical thinking, confidence and professional readiness. The article argues that effective oratory should be based on the unity of content, logic, language culture, ethical responsibility and practical training.